Immunohistochemical evaluation of the GABAergic neuronal system in the prefrontal cortex of a DISC1 knockout mouse model of schizophrenia. Issue 12 (1st August 2016) - Umeda, Kentaro; Iritani, Shuji; Fujishiro, Hiroshige; Sekiguchi, Hirotaka; Torii, Youta; Habuchi, Chikako; Kuroda, Keisuke; Kaibuchi, Kozo; Ozaki, Norio
Abstract: The etiology of schizophrenia remains unknown. However, using molecular biological techniques, some candidate genes have been identified that might be associated with the disease. One of these candidate genes, disrupted‐in‐schizophrenia 1 (DISC1), was found in a large Scottish family with multiple mental illnesses. The function of DISC1 is considered to be associated with axon elongation and neuron migration in the central nervous system, but the functional consequences of defects in this gene have not been fully clarified in brain neuronal systems. Dysfunction of the gamma‐aminobutyric acid (GABA)ergic neuronal system is also considered to contribute to the pathogenesis of schizophrenia. Thus, to clarify the neuropathological changes associated with DISC1 dysfunction, we investigated the number and distribution of GABAergic neurons in the prefrontal cortex of DISC1 knockout mice. We immunohistochemically quantified the laminar density of GABAergic neurons using anti‐parvalbumin and anti‐calbindin D28k antibodies (markers of GABAergic neuronal subpopulations). We found that the densities of both parvalbumin‐ and calbindin‐immunoreactive neurons in the anterior cingulate, medial prefrontal, and orbitofrontal cortices were markedly lower in DISC1 knockout mice than in wild‐type mice. In addition, reductions in cell density were observed in layers II and III and the deep layers of the cortex. This reduction in GABAergic neuronal density was not associated with alterations in neuronal size. These findings suggest that disrupted GABAergic neuronal network formation due to a DISC1 deficit might be involved in the pathophysiology of schizophrenia. Abstract : Using the animal model mice of schizophrenia, the authors have investigated the expression of PV (Parvalbumin) and Calbindin D28k in the prefrontal cortex, and compared to those of wild‐type mice. The densities of both PV‐ and Calbindin‐ neurons were lower in model mice than in wild‐type mice.